Genetic Confirmation of Mungbean (Vigna radiata) and Mashbean (Vigna mungo) Interspecific Recombinants using Molecular Markers - Abbas, Ghulam; Hameed, Amjad; Rizwan, Muhammad; Ahsan, Muhammad; Asghar, Muhammad J.; Iqbal, Nayyer (Frontiers in Plant Science, 2015)
Molecular confirmation of interspecific recombinants is essential to overcome the issues like self-pollination, environmental influence, and inadequacy of morphological characteristics during interspecific hybridization. The present study was conducted for genetic confirmation of mungbean (female) and mashbean (male) interspecific crosses using molecular markers. Initially, polymorphic random amplified polymorphic DNA (RAPD), universal rice primers (URP), and simple sequence repeats (SSR) markers differentiating parent genotypes were identified. Recombination in hybrids was confirmed using these polymorphic DNA markers. The NM 2006 × Mash 88 was most successful interspecific cross. Most of true recombinants confirmed by molecular markers were from this cross combination. SSR markers were efficient in detecting genetic variability and recombination with reference to specific chromosomes and particular loci. SSR (RIS) and RAPD identified variability dispersed throughout the genome. In conclusion, DNA based marker assisted selection (MAS) efficiently confirmed the interspecific recombinants. The results provided evidence that MAS can enhance the authenticity of selection in mungbean improvement program.